Konsentrasi Inhibitori Minimum dan Konsentrasi Fungisidal Minimum Ekstrak dan Nanopartikel Ekstrak Etanol Daun Terompet Emas (Allamanda cathartica L.) terhadap Malassezia furfur - Sabila , Anisa; Rahayu , Yayuk Putri; Nasution , Haris Munandar; Yuniarti , Rafita (Journal of Pharmaceutical and Sciences, 2025)
Background: Fungal skin infections such as pityriasis versicolor caused by Malassezia furfur remain a common health problem in tropical regions. Limitations of conventional antifungal therapy have encouraged the development of alternative agents derived from natural products. Golden trumpet leaves (Allamanda cathartica L.) contain flavonoids and iridoids with potential antifungal activity, and nanoparticle formulations are being developed to enhance the extracts’ effectiveness. Objective: To evaluate the improvement of antifungal efficacy of the nanoparticle formulation of the ethanolic extract of golden trumpet leaves against Malassezia furfur by comparing the Minimum Inhibitory Concentration (MIC), Minimum Fungicidal Concentration (MFC), and inhibition zone diameter with the conventional extract. Methods: This experimental study employed a posttest-only control group design. Treatment groups included ethanolic extract (6.25%, 12.5%, 25%, 50%) and nanoparticle extract (0.625%, 1.25%, 2.5%, 5%). Nanoparticles were prepared using a high-pressure homogenizer and characterized with a Particle Size Analyzer (PSA). MIC and MFC were determined using the broth dilution method, while antifungal activity was assessed using the disc diffusion method. Data were analyzed using one-way ANOVA at a 95% confidence level. Results: Nanoparticle characterization revealed a particle size of 367.51 nm. The MIC values for the extract and nanoparticles were 12.5% and 1.25%, respectively, while the MFC values were 50% and 5%, respectively. The highest inhibition zones for the extract and nanoparticles were 21.1 mm (50%) and 20.3 mm (5%), respectively. Statistical analysis showed significant differences (p < 0.05) in inhibition zone diameters across concentrations for both extract forms. Conclusion: The nanoparticle formulation of the ethanolic extract of golden trumpet leaves significantly enhances antifungal activity against Malassezia furfur, demonstrating equivalent inhibitory effects at concentrations ten times lower than the conventional extract. These findings indicate the potential of nanoparticle-based formulations as promising antifungal candidates.